The Egwaider Type-I Distribution - Egwaider , Mohamed S. A. Muiftah (Scientific Journal of University of Benghazi, 2023)
In this paper the Egwaider Type-I distribution is introduced. It is a discrete distribution generated as a special case of the finite Egwaider distribution. The properties of the resulted discrete distribution are discussed. Some special cases from the resulted discrete distribution are also introduced and some remarks about it are given. Data from this discrete distribution are simulated and used to estimate its shape parameter. Finally, the conclusion and discussion are given.